2020
DOI: 10.1039/d0se00301h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced water oxidation performances of birnessite and magnetic birnessite nanocomposites by transition metal ion doping

Abstract: Co2+ and Ni2+ doped layered birnessite and birnessite-manganese ferrite core–shell catalysts displayed enhanced chemical stability and performance in chemical and electrochemical water oxidation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…Manganese ferrite (MnFe 2 O 4 ) NPs have been studied extensively in many fields involving medicine, drug delivery, and chemical sensing and have offered good potentials in the field of catalysis depending on its being stable, inexpensive, and magnetically recoverable [38][39][40][41][42][43][44]. Despite this interest, no one to the best of our knowledge has studied MnFe 2 O 4 NPs as a core support material for the coating of a plant or a green tea extract for the immobilization of metal nanoparticles to produce an efficient and recoverable catalyst for their potential applications in the related fields so far.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese ferrite (MnFe 2 O 4 ) NPs have been studied extensively in many fields involving medicine, drug delivery, and chemical sensing and have offered good potentials in the field of catalysis depending on its being stable, inexpensive, and magnetically recoverable [38][39][40][41][42][43][44]. Despite this interest, no one to the best of our knowledge has studied MnFe 2 O 4 NPs as a core support material for the coating of a plant or a green tea extract for the immobilization of metal nanoparticles to produce an efficient and recoverable catalyst for their potential applications in the related fields so far.…”
Section: Introductionmentioning
confidence: 99%
“…10a,b) (Hocking et al , 2011; Robinson et al , 2013; Lucht and Mendoza-Cortes, 2015; Thenuwara et al , 2015; Yang et al , 2015). Consequently, the photo-oxidation activity of birnessite has drawn increasing attention, especially for water oxidation (Hocking et al , 2011; Wiechen et al , 2012; Thenuwara, et al, 2015; McKendry et al, 2018; Elmacı et al , 2020).
Fig.
…”
Section: Photo-reactivity Of Natural Semiconducting Mn Oxidesmentioning
confidence: 99%
“…7,[11][12] Additionally, dopants can improve the catalytic activity of δ-MnO2 by enhancing its redox properties and lattice oxygen mobility and reactivity through the reduction of charge transfer resistance. [13][14] Due to their similar ionic radii, Cobalt (Co) was shown to effectively incorporate into the octahedra of δ-MnO2 by substituting Mn 4+ leading to the creation oxygen vacancies. 10 Elmaci et al 13 explored various transition metals as dopants for δ-MnO2 and demonstrated that, compared to the pristine δ-MnO2, Co-doped δ-MnO2 exhibited enhanced catalytic activity and chemical stability for water oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] Due to their similar ionic radii, Cobalt (Co) was shown to effectively incorporate into the octahedra of δ-MnO2 by substituting Mn 4+ leading to the creation oxygen vacancies. 10 Elmaci et al 13 explored various transition metals as dopants for δ-MnO2 and demonstrated that, compared to the pristine δ-MnO2, Co-doped δ-MnO2 exhibited enhanced catalytic activity and chemical stability for water oxidation reaction. This is due to the substitution of Mn 4+ by Co 3+ in the octahedral framework of δ-MnO2 leading to an increase in the ration of Mn 3+ /Mn 4+ .…”
Section: Introductionmentioning
confidence: 99%